Development and systematic evaluation of high resolution PD‐weighted, T2‐weighted, and T2 map templates of the MIITRA atlas for use in studies on older adults. (20th December 2022) - Ridwan, Abdur Raquib; Niaz, Mohammad Rakeen; Wu, Yingjuan; Zhang, Shengwei; Bennett, David A; Arfanakis, Konstantinos
Abstract: Background: Atlas based MRI investigations involving PD‐weighted (PDw), T2‐weighted (T2w) MRI sequences on older adults typically utilized younger adult templates such as those of the ICBM. Additionally, a thorough quantitative assessment of how available standardized PDw and T2w templates perform on aging population has not yet been performed. Here a new standardized high resolution PDw, T2w and T2 map templates of the MIITRA atlas dedicated for studies on older adults was developed using concepts of super‐resolution and sparse‐representation and compared to other available standardized templates in terms of image quality, inter‐subject spatial normalization accuracy and representativeness of the older adult brain. Method: T2‐weighted multi‐echo spin‐echo brain MRI (0.5mmx0.5mmx3mm isotropic, TE=20, 40, 60, 80, 100ms) and its corresponding T1‐weighted (isotropic 1mm) data obtained from the 400 non‐demented older adults (65‐95 age range, male:female=1:1) participating in the construction of the MIITRA atlas were used in this work. Additionally, subject T2 maps were constructed by fitting the T2 decay equation. The template construction involved reconstruction of high resolution voxels of T2‐weighted data utilizing nonlocal super‐resolution upsampling technique, mapping of each of the five echo (TE=20, 40, 60, 80, 100ms) separately using combined iterative T1‐weighted and DTI spatial normalization based transformations on a super‐resolution grid followed by patch‐based sparse representation to construct our T2‐weighted templates of the MIITRA atlas (Fig.1).The first echo PD‐weighted and the third echo T2‐weighted templates were compared to other available templates in terms of image sharpness and inter‐subject spatial normalization accuracy achieved when used as references for normalization of 30 ADNI PD‐weighted and T2‐weighted participants. Result: The new PD and T2 weighted templates of the MIITRA atlas demonstrated higher image sharpness compared to the other templates, as exhibited by larger high spatial frequency content in the normalized power spectra (Fig. 2A, B, C, D). Inter‐subject spatial normalization was higher when using the new templates compared to the other templates (Fig.3, 4). The new templates required the least spatial deformation for normalizing ADNI data (Fig.5A, B). Conclusion: We conclude that the new PD‐weighted and T2‐weighted templates of the MIITRA atlas are characterized by superior image quality, require lower deformation and allow for higher spatial normalization accuracy for use in studies on older adults such as the ADNI datasets.